2002
DOI: 10.1182/blood-2001-12-0303
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of ILT2/CD85j in Sézary syndrome cells inhibits their CD3/TCR signaling

Abstract: Extensive phenotype analysis of cutaneous T-cell lymphoma (CTCL) malignant cell lines revealed surface expression of receptors usually not detected on normal circulating CD4 ؉ CD45RO ؉ lymphocytes. We previously found that CTCL malignant cells express the killer cell immunoglobulinlike receptor (KIR) KIR3DL2/CD158k, whereas they fail to express the other KIRs. In the present study, we report for the first time that the CD85j/immunoglobulin (Ig)-like transcript 2 (ILT2) receptor is found on Sé zary cell lines a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 42 publications
1
19
0
2
Order By: Relevance
“…Further downstream of the TCR, we identified a loss of PLCg-1 activation that leads to reduced ROS production and abrogated intracellular Ca 2+ release specifically in CTCL cells. In line with our findings, Nikolova and colleagues (28) suggested that the reduction of TCR signaling by inhibitory receptors (CD158k/KIT3DL2 and CD85j/ILT-2R) may lead to AICD resistance as seen in ILT-2R-expressing T cells. The finding of reduced TCR signaling in CTCL cells was also reported by Fargnoli and colleagues (29) who showed decreased activities of Zap70, Syk and membraneassociated Csk after TCR stimulation.…”
Section: Discussionsupporting
confidence: 79%
“…Further downstream of the TCR, we identified a loss of PLCg-1 activation that leads to reduced ROS production and abrogated intracellular Ca 2+ release specifically in CTCL cells. In line with our findings, Nikolova and colleagues (28) suggested that the reduction of TCR signaling by inhibitory receptors (CD158k/KIT3DL2 and CD85j/ILT-2R) may lead to AICD resistance as seen in ILT-2R-expressing T cells. The finding of reduced TCR signaling in CTCL cells was also reported by Fargnoli and colleagues (29) who showed decreased activities of Zap70, Syk and membraneassociated Csk after TCR stimulation.…”
Section: Discussionsupporting
confidence: 79%
“…It is detected on the surface of a proportion of T cells (19,20) and in the cytoplasm of all T lymphocytes (21). Cytoplasmic expression of CD85j in all CD4 ϩ T cells has been recently confirmed (22). CD85j is functional in all T cells, independently of its surface expression (21), and it down-regulates Ag-specific functions of T lymphocytes (21,23).…”
mentioning
confidence: 96%
“…ILT2 triggering induces phosphorylation of intra-cytoplasmic ITIMs, which become docking sites for the SHP-1 and SHP-2 phosphatases [16,17]. Once recruited to the NK/tumor cell interface, the SHP-1 and SHP-2 phosphatases disable activatory signal transduction pathways through the dephosphorylation of signaling components, ultimately leading to inhibition of NK-cell activation.…”
Section: Introductionmentioning
confidence: 99%